Effect of nikel on growth and ultrastructure of Schizosaccaromyces pombe - ERCAN, FERİHA (TAYLOR & FRANCIS LTD, 2001)
In this project, we investigated effects of nickel (Ni) on the growth and ultrastructure of Schizosaccharomyces pombe wild type strain. It was found that cells were tolerant against a concentration of 2 mM Ni+2 but the generation time was extended to 5 hours from 2.5 hours for the cells growing in Ni-free YEP medium. 76% of Ni+2 was removed in 30 min by the cells grown in YEP containing 1mM Ni+2. We also analyzed the ultrastructural modifications of the cells grown in 1 mM Ni+2. There was a visible thickening of the cell wall and increase in the number of small cytoplasmic vesicles. The plasma membrane appeared irregular compared to smoother contour in control. Vacuoles contained large amounts of electron-dense materials and the size of vacuoles also increased.
Keywords: NICKEL; YEAST; BIOSORPTION; METALS